Distribusi Spasial dan Temporal Nutrien di Danau Tempe, Sulawesi Selatan - Siti Aisyah; Sulung Nomosatryo, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Spatial and Temporal Distribution of Nutrient in Lake Tempe, South Sulawesi. The concentration of nutrients in the process of eutrophication have an important role in the freshwater productivity. Lake Tempe constitutes a conservation area for water resources that has been degraded, indicated by high sedimentation and abundant water weeds. This resulted in the lowered carrying capacity of the lake. This study aimed to determine the concentration and spatiotemporal distribution of nutrients in Lake Tempe as the basis for the management of the lake. Water samples were taken using Kemmerer water sampler in April, July, and October 2013 from seven stations. Dissolved oxygen, pH, temperature, and transparency were measured in situ, while the N-Nitrite, N-Nitrate, N-Ammonium, TN, orthophosphate, and TP as well as supporting parameters such as COD, TOM, and chlorophyll-a were analyzed in the laboratory using methods according to the Standard Method. The study showed the concentrations of N and P were varied at all observation sites. The concentrations of N-Nitrate, TN, and TP tended to be high in October, while the concentrations of N-Nitrite, N-Ammonium, and orthophosphate tended to be high in April. PCA analysis showed the water quality conditions in Lake Tempe were characterized by the N and P compounds. The high average concentrations of TN and TP in Lake Tempe with respective values of 1.386 mg/L and 0.198 mg/L indicated that the lake was a productive lake, classified as eutrophic with nitrogen as limiting factor of lake fertility. If the nutrient enrichment continues, it will have a negative impact on the water quality of the lake